Perbandingan Uji Aktivitas Antibakteri Kunyit, Jahe, dan Bawang Putih - falan ndilai (Journal of Innovative Food Technology and Agricultural Product, 2025)
The use of natural ingredients as antibacterial agents has gained increasing attention in the food sector, particularly as alternatives to synthetic preservatives that may pose health risks. Turmeric, ginger, and garlic are spices known to contain bioactive compounds with antibacterial properties. This study aimed to compare the antibacterial activity of turmeric, ginger, and garlic extracts against foodborne pathogenic bacteria. The disc diffusion method was employed using ethanol as a solvent, and the parameter observed was the diameter of the bacterial growth inhibition zone. The results showed that garlic extract exhibited the highest antibacterial activity with an inhibition zone diameter of 13.40 ± 0.42 mm and was categorized as strong, followed by turmeric extract with 10.20 ± 0.35 mm categorized as moderate, and ginger extract with 8.50 ± 0.28 mm categorized as weak. The positive control chloramphenicol produced an inhibition zone of 18.60 ± 0.50 mm, while the negative control ethanol showed no inhibition zone. The differences in antibacterial activity were presumably influenced by the type and concentration of bioactive compounds present in each material. It can be concluded that all three materials have potential as natural antibacterial agents, with garlic showing the highest effectiveness. Keywords: natural antibacterial, turmeric, ginger, garlic.